Pandangan Abraham Maslow tentang Memanusiakan Manusia untuk Pemaknaan pada Era Modern di Indonesia - Siti Latifah Agistiani (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss Abraham Maslow's views on humanizing humans for meaning in the modern era in Indonesia. This study uses a qualitative approach by applying the method descriptive-analytical. The formal object of this research is the view of Abraham Maslow, while the material object is humanizing humans. The scope of research is in the modern era. The rest, the context of this research is in Indonesia. The results and discussion in this study indicate that education is the beginning of the formation of a child's character with the aim of humanizing humans. Education in Indonesia has also initiated an independent learning program